Fabrication and Characterization of Piezoelectric Polymer Nano Composites for Humidity Sensors Applications - Jabbar Braihi, Auda; Amir Flaieh, Ahmed; Mohammed Hussein, Mostafa (International Journal of Engineering and Technology, 2018)
Piezoelectric polymer nano compositesfor humidity sensors applications are manufactured in this work by adding nano Yttrium oxides (Y2O3) in three ratios (3,6and 9 wt.%) to the polymeric blend consist of (1:9) poly vinyl difluoride (PVDF) and poly methyl methacrylate (PMMA). FTIR results showed that PVDF addition to PMMA causes shifting in the blue direction and there is no chemical bonding between the prepared composites components,butthere is a significant increase in the rate of permeabilityat higherY2O3 ratio. This addition causes the hardness to be increased linearly. Morphology results showed, that the lower ratios of Y2O3 causes the surface became smoother and homogeneous, while higher ratios increase the roughness of the surface. These compositesgive piezoelectric behavior where the electrical resistance decreases by increasing the pressure. With regard to the dielectric properties the losses coefficient increase by increasing the frequency while dielectric constant decreases. The composites showed to be more hydrophilic by increasing theY2O3 ratio,which suggests these composites for water storage applications. The results show possibility of using these composites as humidity sensorsin relative humidity less than 70%, where the electrical resistivity decreases as the relative humidity increasing.Â Â